Pengembangan Karakter Kemandirian Anak Usia 2 – 4 Tahun di Kelompok Bermain - Hasanah, Dzulia; Rakimahwati, Rakimahwati (Universitas Negeri Padang, 2020)
This study aims to determine the implementation of the character development of early childhood independence. Independence is one of the character values that needs to be developed by early childhood. The research method used is literature study. Data collection techniques by examining primary sources in the form of reference books and journals that are relevant to the research problem. After getting the required data then the next is analyzing the data. The analysis is done by connecting the problem with relevant concepts and theories. The research findings show that the development of the character of independence in children can be done using the Montessori method that prioritizes freedom in children. The results of the study are based on the findings of the Pratical life learning in the Montessori method to develop the character of independence in early childhood